Epidemiological, Clinical, and Trichoscopic Features of Syphilitic Alopecia: A Retrospective Analysis and Systematic Review - Pomsoong, Cherrin; Sukanjanapong, Siriorn; Ratanapokasatit, Yanisa; Suchonwanit, Poonkiat (Frontiers in Medicine, 2022)
Background: Syphilitic alopecia (SA), which mimics other types of alopecia, is an uncommon manifestation of secondary syphilis. Trichoscopic features may facilitate its diagnosis. However, studies on SA and its trichoscopic characteristics remain limited. Objective: To investigate the epidemiological, clinical, and trichoscopic findings and laboratory results, treatment, and outcomes of SA in Thai patients as well as to comprehensively summarize all trichoscopic features of SA through a systematic review. Methods: Data on patients diagnosed with SA between December 2010 and December 2021 were obtained from their medical records and analyzed retrospectively. A systematic review of trichoscopic data, both from our institution and from studies registered in the PubMed, MEDLINE, and Embase databases, was conducted. A descriptive summarization was performed to comprehensively study the trichoscopic features of SA. Results: Of the 205 patients with secondary syphilis, 23 patients with SA (symptomatic SA: 20, essential SA: 3) were included. The mean age was 27.6±8.8 years, and male predominance was noted. The moth-eaten pattern was the most common SA presentation, and the parieto-occipital scalp was the most commonly affected area. All patients with SA achieved significant hair regrowth within 3 months of antibiotic therapy. Trichoscopic images were available for 20 patients with SA from our institute and were included in the systematic review. Fourteen articles provided information on 21 patients. Overall (N=41), 26 (63.4%), 8 (19.5%), and 7 (17.1%) patients had moth-eaten alopecia, diffuse alopecia, and mixed alopecia, respectively. The most frequent trichoscopic finding was short regrowing hairs (78%), followed by decreased hair per follicular unit (75.6%), and empty follicles (51.2%). Unique features included flame hairs, bent tapering hairs, reddish-brown background, and brown rings around the perifollicular areas, each described in one case. However, the results were based only on case reports and small case series. Conclusions: Given the progressively increasing frequency of SA, trichoscopic examination may be valuable when SA is suspected in patients with idiopathic alopecia; however, our findings are quite non-specific. The absence of exclamation mark hairs may help in the diagnosis of SA. Further comparative studies on other types of alopecia are required to determine the most useful diagnostic features.